Production potential of sorghum (Sorghum bicolor) intercropped with pigeonpea (Cajanus cajan) under varying fertility levels in the rainfed environment of Bundelkhand region - Tripathi, A.K.; Kushwaha, H.S. (Annals of Agricultural Research, 2016)
A field experiment was conducted during rainy seasons of 2004-05 and 2005-06 at Agriculture Research Farm, Nehru P.G. College, Lalitpur (U.P.) in sandy loam soil, to find out optimum NPK fertilizer requirement of sorghum + pigeonpea intercropping system. The seed yield of intercrop sorghum was significantly superior at sorghum with 75% NPK + pigeonpea with RDF (1.76 t/ha). Plant height, length and width/panicle, seeds/ panicle of intercrop sorghum were also distinctly higher with these treatment combinations. Sorghum equivalent yield was 108.13% higher at sorghum 75% NPK + pigeonpea RDF over sole sorghum at RDF with LER value of 1.80. Protein content of sorghum seed did not significantly vary due to intercropping system. . However, N,P,Kuptake was 5.32, 16.36 and 14.22 % higher with sorghum + pigeonpea at sorghum 75% NPK+ pigeonpea RDF over sole sorghum at RDF.